Nasakh dalam Sunah Implikasinya bagi Hukum Islam dan Tafsir Al-Qur’an - Ahmad Taqiyuddin Takdir; Teguh Arafah Julianto; Nurul Hasanah (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2025)
This article examines the concept of nasakh (abrogation) in the Sunnah of Prophet Muhammad Saw and its implications for Islamic law and Qur’anic exegesis. Nasakh is understood as the abrogation of an existing legal ruling by a subsequent one, based on a clear and authoritative Sharī‘ah evidence. The phenomenon of nasakh in the Sunnah can be found in several hadiths, such as the prohibition of visiting graves which was later permitted, the initial restriction on storing sacrificial meat for more than three days which was subsequently lifted, the allowance and later prohibition of temporary marriage (nikah mut‘ah), the prohibition and later allowance of using certain containers for wine, and the obligation of qiyam al-lail (night prayer) which was later reduced to a recommended practice. This study employs a library research method with descriptive-analytical and historical-normative approaches. The findings reveal that nasakh in the Sunnah plays a crucial role in maintaining the flexibility of Islamic law, resolving textual contradictions, and demonstrating the principle of tadarruj (gradualism) in legislation. Moreover, hadiths containing nasakh have significant implications for interpreting Qur’anic legal verses, making the study of nasakh an integral part of Islamic legal and exegetical scholarship.